Politiche per la centralità della montagna - Fiorenzo Ferlaino (Scienze del Territorio, 2021)
The article briefly traces back the development of policies dedicated to the mountain regions of Italy from the post-war era to the present day, browsing from ‘depressed territories’, to ‘disadvantaged areas’ and ‘mountain communities’, up to the recent Inland Areas National Strategy. The underlying idea is that such place-based policies are ineffective if not supported by a great labour reform, a regeneration of boroughs and a reuse of abandoned woods apt to redirect towards the mountains most of the (public and private) operators active via teleworking or smart working. All these policies should be built, programmed, planned to prevent ‘spontaneous development’ logics from destroying (as already happened in coastal areas) the mountains landscape and resources. In other words, we should avoid that the new centrality of mountains forced by climate change (and by the rising concern of new pandemics) may generate new phenomena such as uncontrolled growth or deterritorialisation which can undermine the path towards sustainability.